Pencegahan Tindak Pidana Korupsi melalui Pengawasan Internal dan Penegakan Kode Etik Aparat Pemerintah - Iwan Ridwan (CV Rewang Rencang, 2025)
This research analyzes the ethical issues of government officials from a public administration perspective, whichplays a crucial role in realizing good governance. The study aims to thoroughly examine the role of internalsupervisors in preventing corruption in government agencies, as well as how ethical violations and lawenforcement relate to corruption cases involving public officials in Indonesia. This research employs a normativejuridical methodology, requiring analysis and examination of secondary data. The research conducted by theauthor, in line with the normative juridical approach, utilizes literature reviews. The role of InternalSupervisory Apparatus (APIP) is very important in achieving clean and transparent governance.Strengthening capabilities and applying strict and fair ethical sanctions are the main factors in enhancingaccountability while building public trust in the public sector.